The establishment of preliminary safety threshold values for cyanobacteria based on periodic variations in different microcystin congeners in Lake Chaohu, China. Issue 4 (18th March 2015) - Shang, Lixia; Feng, Muhua; Liu, Feifei; Xu, Xiangen; Ke, Fan; Chen, Xiangchao; Li, Wenchao
Abstract : It is necessary to establish periodic safety threshold values for cyanobacteria referring to the main MC congeners rather than MC-LR. Abstract : As harmful cyanobacterial proliferation threatens the safety of drinking water supplies worldwide, it is essential to establish a safety threshold (ST) for cyanobacteria to control cyanobacterial density effectively in water sources. For this purpose, cyanobacterial abundance, microcystin (MC) production, and environmental parameters were monitored monthly from September 2011 to August 2012 in one drinking water source of Lake Chaohu. The cyanobacterial density ranged from 1400 to 220 000 cells per mL with the succession of two dominant species Microcystis and Dolichospermum, which was determined by water temperature and nutrient loading. The MC concentrations were correlated significantly with the cyanobacterial density and they varied between 0.28 and 8.86 μg L −1 . Therefore, the characteristics of MC cell quotas were classified according to four stages of the development of cyanobacteria, namely: recruitment, multiplication, decline and dormancy. The ST for cyanobacteria was established for different periods based on the MC cell quota and its guideline wherein three commonly monitored MC congeners (MC-LR, -RR and -YR) were considered in the present study. Its reliability was verified in the water source using the data collected between June 2013 and May 2014. The results highlighted the necessity to classify the ST-values in different periods referring to the main MC congeners rather than MC-LR, which will facilitate the management and control of toxic cyanobacterial proliferation in drinking water sources.